Cremation and Grief: Are Ways of Commemorating the Dead Related to Adjustment Over Time?. (August 2020) - Birrell, John; Schut, Henk; Stroebe, Margaret; Anadria, Daniel; Newsom, Cate; Woodthorpe, Kate; Rumble, Hannah; Corden, Anne; Smith, Yvette
Funeral services are known to serve multiple functions for bereaved persons. There is also a common, intuitively reasonable assumption of positive associations between engaging in funeral activities and adjustment to bereavement. We examined whether restricting ceremonial cremation arrangements to a minimum has a negative association with grief over time. Bereaved persons in the United Kingdom completed questionnaires 2 to 5 months postloss and again a year later ( N = 233 with complete data; dropout = 11.4%). Neither type nor elaborateness of the cremation service, nor satisfaction with arrangements (typically high), emerged as significantly related to grief; no major subgroup differences (e.g., according to income level) were found. Results suggested that it does not matter to grief whether a more minimalistic or elaborate funeral ceremony was observed. We concluded that the funeral industry represented in this investigation is offering bereaved people the range of choices regarding cremation arrangements to meet their needs. Limits to generalizability are discussed.